1997
DOI: 10.1097/00002030-199707000-00001
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of interventions to reduce mother-to-child transmission of HIV in the United Kingdom and Ireland

Abstract: Although detection of previously undiagnosed HIV infection in pregnancy remains low in the United Kingdom, and particularly in London, HIV-infected pregnant women who are aware of their status are increasingly active in taking up interventions to reduce transmission to their infants. If all HIV-infected women attending for antenatal care in London consented to testing and took up interventions and termination of pregnancy at the rates observed in this study, the number of vertically infected babies born in Lon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0
1

Year Published

1998
1998
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 16 publications
1
38
0
1
Order By: Relevance
“…Although the literature suggests that the figure might be as high as 20% [59], this finding was derived from data obtained between 1990 and 1995, a time before the effectiveness of antiretroviral therapies had been fully realized and when the risks of vertical transmission were still considerable. The value that we used was obtained from data obtained in 1999 and, we argue, is a more accurate reflection of current practice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the literature suggests that the figure might be as high as 20% [59], this finding was derived from data obtained between 1990 and 1995, a time before the effectiveness of antiretroviral therapies had been fully realized and when the risks of vertical transmission were still considerable. The value that we used was obtained from data obtained in 1999 and, we argue, is a more accurate reflection of current practice.…”
Section: Discussionmentioning
confidence: 99%
“…However, for all scenarios, we assumed that the uptake of screening would remain at 95% and that informed consent would be obtained in an ethical manner. The literature [45,59,[66][67][68][69][70][71][72][73][74][75] suggests that high compliance and ethical screening is determined by careful and sensitive pretest counselling, the level of training for each health-care professional, a need to take particular care when English is not the first language (in countries where English is the most commonly spoken language), and the age, attitudes, and experience of the health-care professionals. On the basis of this, we recommend that appropriate investments be made in continuing professional education.…”
Section: Discussionmentioning
confidence: 99%
“…22 A UK/Ireland study found that pregnancy termination rates among HIV-positive women remained steady before and after the introduction of PMTCT programmes. 23 Still other research has shown that more HIV-positive women are now choosing to carry pregnancies to term. One US study compared women's decisions to have a tubal ligation or abortion before and after the introduction of PMTCT; while sterilisation rates remained unchanged, fewer women chose to terminate their pregnancies after antiretroviral therapy became available during pregnancy.…”
mentioning
confidence: 99%
“…However, uptake of testing is no diVerent between black and white women in London, 20 and failing to oVer testing to black African women is discriminatory in denying those who are the most likely to benefit. 21 Currently, in London, antenatal testing is rarely routine. 22 Unlike for other infections, such as rubella, syphilis, and, now, hepatitis B, 23 testing has to be explicitly sought or oVered and is often contingent on discussion of the risk factors.…”
Section: Director Of Research and Development Anglia And Oxford Region mentioning
confidence: 99%